Mendelian randomization analysis of immune cell characteristics and genetic variants in cervical cancer risk: a genome-wide association study - Yu Zhang; Limei Ji; Shuo Yang (Discover Oncology)
Abstract Background Cervical cancer remains a significant global health concern, with both genetic and immunological factors potentially influencing susceptibility. This study aimed to investigate the causal relationships between immune cell characteristics, genetic variants, and cervical cancer risk using Mendelian randomization (MR) analysis. Methods We utilized genome-wide association study (GWAS) data from the UK Biobank, comprising 475,638 participants of European descent with approximately 24.2 million genetic variants. Instrumental variables were selected at a significance threshold of 1 × 10^-5 for immune characteristics. Results Forest plot analysis of genetic variants revealed minimal associations with cervical cancer risk, with most odds ratios close to 1.000 despite some statistically significant findings (p < 0.05). MR analyses demonstrated consistent negative correlations between SNP effects on certain immune cell populations and cervical cancer risk, though effect sizes remained small. Multiple MR methods produced similar summary estimates, suggesting no substantial causal relationship between the studied immune cell characteristics and cervical cancer susceptibility. Conclusions This comprehensive MR analysis found limited evidence for causal associations between immune cell-related genetic variants and cervical cancer risk. While some statistically significant relationships were observed, the effect sizes were notably small, indicating that these genetic determinants of immune.